2019
DOI: 10.21873/invivo.11530
|View full text |Cite
|
Sign up to set email alerts
|

Pedicle Periosteum as a Barrier for Guided Bone Regeneration in the Rabbit Frontal Bone

Abstract: Background/Aim: For alveolar ridge reconstruction prior to dental implant placement, a barrier membrane is placed to create space over the bone defect. Although periosteum possesses osteogenic capacity, direct contact between defects and periosteum has been avoided. The present study aimed to investigate whether pedicle periosteum could be used as a barrier membrane. Materials and Methods: Twelve rabbits were used. A U-shaped incision was made in the frontal bone, and the skin-periosteum over the frontal bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…[ 129 ] Biologic materials composed of mammalian ECM have been effectively used for the repair and reconstruction of a variety of tissues, including skeletal muscle, [ 130–132 ] esophagus, [ 133–135 ] and heart, [ 136–138 ] among others. Barrier membranes for GBR applications have been successfully fabricated using various biological sources, such as pedicle periosteum, [ 139 ] leukocyte‐ and platelet‐rich fibrin (L‐PRF), [ 140 ] and small intestinal submucosa (SIS). In particular, multilaminate small intestinal submucosa (mSIS) [ 141 ] consisted in a stack of eight lyophilized layers of acellular porcine SIS.…”
Section: Gbr Strategies and New Membranes Under Preclinical Evaluationmentioning
confidence: 99%
“…[ 129 ] Biologic materials composed of mammalian ECM have been effectively used for the repair and reconstruction of a variety of tissues, including skeletal muscle, [ 130–132 ] esophagus, [ 133–135 ] and heart, [ 136–138 ] among others. Barrier membranes for GBR applications have been successfully fabricated using various biological sources, such as pedicle periosteum, [ 139 ] leukocyte‐ and platelet‐rich fibrin (L‐PRF), [ 140 ] and small intestinal submucosa (SIS). In particular, multilaminate small intestinal submucosa (mSIS) [ 141 ] consisted in a stack of eight lyophilized layers of acellular porcine SIS.…”
Section: Gbr Strategies and New Membranes Under Preclinical Evaluationmentioning
confidence: 99%
“…The inner osteogenic (cambium) layer, which lies adjacent to the bone, has a high cellular density, including osteoclasts. ( Frey, et al, 2013 , Hasuike et al, 2019 )…”
Section: Discussionmentioning
confidence: 99%
“… Hasuike et al 2019 described the use of the periosteum as a barrier for guided bone regeneration. The pedicle periosteum placed just above the bone defect acts more as a barrier rather than a resource of fibrous tissue in bone defects.…”
Section: Discussionmentioning
confidence: 99%
“…Our group examined the effects of the pedicle periosteum on bone regeneration in a rabbit calvarial-bone-defect model. Histological sections showed that the periosteum contributes to the formation of new bone by acting as a mechanical barrier and source of osteogenic factors [ 22 ]. From this perspective, our present approach using the periosteum tab would optimally utilize the properties of the periosteum.…”
Section: Discussionmentioning
confidence: 99%